Synthesis and Characterization of PANI/ZnO Composites: Structure and Conductivity Analysis Supervised - Nasution, Fitri Khairani; Yuningsih, Lela Mukmilah; Anwar, Devi Indah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Technological advances have accelerated the development of functional materials for sensing applications. Polyaniline (PANI) is a conductive polymer with attractive electrical properties, but its gas-sensing performance remains limited. This study aimed to synthesize a PANI/ZnO composite and evaluate its structural and electrical characteristics as a potential gas-sensing material. The composite was prepared by interfacial polymerization and characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and electrical conductivity measurements. FTIR and XRD analyses confirmed the successful formation of the PANI/ZnO composite through the presence of characteristic functional groups and crystalline phases of both PANI and ZnO, indicating effective interaction between the two materials. The composite exhibited an electrical conductivity of 1.038 × 10⁻⁵ S/cm, demonstrating semiconducting behavior suitable for sensing applications. The incorporation of ZnO into the PANI matrix is considered to improve the structural characteristics of the composite while maintaining its electrical conductivity. These findings confirm the successful synthesis of the PANI/ZnO composite and indicate its potential as an active material for gas sensor development. Nevertheless, further studies are required to evaluate its gas-sensing performance, including sensitivity, selectivity, response time, and long-term stability under various operating conditions.